Wajah Agama dalam Tradisi Pelet Bettheng Masyarakat Madura - Zaitur Rahem (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Strong building a community is cultural. Humans can not be separated from the culture created. Every generation has its cultural achievements of each. The cultural movement gradually transformed mindset, character and ideology. Centrals culture itself has been represented by rural areas. The village with all the trappings of his life, was able to survive and meruwat kebudyaannya, despite continued menggempurnya times with a number of technological progress and civilization. Derap culture in rural areas also ignited masarakat confidence in Indonesia to build a distinctive civilization nusantaranya. All local wisdom in the area of the archipelago is an insight into life. One of the cultural appearance of the wise is in the village of pellets bettheng Pajudan Daleman and Village Rombasan. These two villages representing the portrait of a civilized life in the island of Madura.Keywords: Pelet Bettheng, Tradisi.